Agro-morphological traits and harvest period assessment of winged bean (Psophocarpus tetragonolobus) genotypes for pods production - Sayyidah Afridatul; MUHAMAD SYUKUR; TRIKOESOEMANINGTYAS TRIKOESOEMANINGTYAS; AWANG MAHARIJAYA (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ishthifaiyyah SA, Syukur M, Trikoesoemaningtyas, Maharijaya A. 2021. Agro-morphological traits and harvest period assessment of winged bean (Psophocarpus tetragonolobus) genotypes for pods production. Biodiversitas 22: 1069-1075. Winged bean (Psophocarpus tetragonolobus) is an underutilized crop in Indonesia. Winged bean varieties for pods productions not only must have high productivity and nutrient contents, but also have a long harvest period. This research aimed to evaluate agro-morphological traits and harvest period of eighth-generation winged bean genotypes. Twenty genotypes of winged beans were evaluated using randomized complete block design (RCB) with three replications in Bogor, Indonesia. Several qualitative and quantitative traits were evaluated from each genotype. The results showed that there were variations among winged bean genotypes which were based on qualitative traits as well as the color of stem, calyx, corolla, pod, and pod wings. Purple coloration in the calyx of P1 and H3U genotypes was known to correspond with the purple color in stem, corolla, pod, and pod wings. The highest yield among F8 genotypes was found in H2 (6.69 to ha-1), similar to P2. However, the longest harvest period among F8 genotypes was found in H1U-2 (78 days). This study revealed that harvest period had positive correlation with the leaflet size. Based on nutrient content, H3U and L2 were considered as the genotypes with the highest protein and fiber content respectively among F8 genotypes.